(untitled) (CAHIERS MAGELLANES-NS, 2024)
In search of potent antimicrobial agents new 1,2,3-triazoles have been synthesized from 4-(diethylamino)-2-hydroxybenzaldehyde. The newly synthesized 1,2,3-triazoles synthesized starting from 4-(diethylamino)-2-hydroxybenzaldehyde. 4-(Diethylamino)-2-hydroxybenzaldehyde (1) was reacted with propargyl bromide (2) in N,N-dimethylformamide in the presence of potassium carbonate as a base to obtain a key intermediate, 4-(diethylamino)-2-(prop-2-yn-1-yloxy)benzaldehyde (3). This alkyne (3) was then condensed with freshly prepared phenyl azides (4a-j) in presence of CuSO4 and sodium ascorbate by following click chemistry approach to obtain better to excellent yields of the titled compounds (5a-j). All the newly synthesized compounds were thoroughly characterized by using 1H NMR, 13C NMR and HRMS analyses.